Exponential inequalities : equality law in times of crisis - Atrey, Shreya, 1988-; Fredman, Sandra (Oxford : Oxford University Press, 2023)
This edited volume addresses the operation of equality and discrimination law in times of crisis. It seeks to understand how existing inequalities are exacerbated in crises and whether equality law has the tools to understand and address this.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Equality before the law; Discrimination -- Law and legislation; International law and human rights; COVID-19 Pandemic, 2020- -- Law and legislation; COVID-19 Pandemic, 2020- -- Social aspects; COVID-19 Pandemic, 2020- -- Economic aspects; Law; Laws of specific jurisdictions & specific areas of law